Evaluation of treatment outcomes of patients with MRSA bacteremia following antimicrobial stewardship programs with pharmacist intervention. Issue 3 (8th February 2018) - Ohashi, Kengo; Matsuoka, Tomoko; Shinoda, Yasutaka; Fukami, Yasuyuki; Shindoh, Joe; Yagi, Tetsuya; Yoshimura, Tomoaki; Sugiyama, Tadashi
Summary: Background: Methicillin‐resistant Staphylococcus aureus bacteremia (MRSA‐B) is associated with high mortality and implementing an appropriate antimicrobial stewardship (AS) program with treatment intervention is essential. The aim of this study was to evaluate the impact of AS with pharmacist intervention on patients with MRSA‐B. Methods: Patients who were diagnosed with MRSA‐B between January 2012 and April 2013 were defined as the pre‐intervention group, while those diagnosed between May 2013 and December 2015 were defined as the intervention group (ie, AS with pharmacist intervention). The factors affecting bundle compliance rates and mortality were analysed. Result: The pre‐intervention group comprised 43 patients and the intervention group comprised 51 patients. Bundle compliance rates were estimated as follows in the intervention group: an increase was observed in the appropriate duration of therapy (from 44.8% to 72.1%, P = .027), incidences of the early use of anti‐MRSA drugs (from 62.3% to 82.4%, P = .038), and the number of negative follow‐up blood cultures (from 40.0% to 80.0%, P < .001), and a decrease was observed for 30‐day mortality (from 41.8% to 21.6%, P = .044) and hospital mortality (from 58.1% to 27.5%, P = .003). In multivariate analysis, the intervention group was independent of 30‐day mortality and hospital mortality risk reduction factors (odds ratio [OR], 0.33; 95% confidence interval [CI], 0.12‐0.86, and OR, 0.20; 95% CI, 0.07‐0.53). Conclusions: AS programs with pharmacist intervention improve mortality in patients with MRSA‐B.